Muslim Youth Between Pragmatism, Islamic Concern, And Social Piety - Fauzi, Muhammad Latif; Pribadi, Yanwar (Universitas Islam Negeri Mataram, 2024)
During the last couple of years, Gen Z youths born between 1997 and 2010 have been actively involved in various social communities promoting a particular understanding of Islam, such as volunteers, frontline activists, or organizers. This article explores their socio-religious activism in Solo and their understanding of Islam. It delves into religious and social piety in their da‘wah (proselytization). We found out that the majority of this generation does not understand the meaning of moderate Islam properly. However, their perspectives and attitudes do not oppose differences. Most of them obtain their religious sources from social media and the Internet. Only a few of them, due to their lack of knowledge of Islamic teachings and limited encounters with non-Muslims, have a hateful attitude towards people of other religions. Meanwhile, they have an excessive defense of Islam. This study confirms Pattana Kitiarsa’s idea that religion has been commodified as a spiritual market where Muslims can select products symbolically associated with Islam.